I have a script that works beautifully that has the following function definitions:
phi(x,y) = (1+x)/(1+sqrt(1+(x*x-1)*y))
astig(n,x,y) = phi(x,y)*(1-phi(x,y)*y)*(n-1)**2-(phi(x,y)-n*n)*(n-1+y*(phi(x,y)-n))**2
It would be a lot cleaner if the following was possible:
phi(x,y) = (1+x)/(1+sqrt(1+(x*x-1)*y))
astig(n,x,y) = f=phi(x,y) f*(1-f*y)*(n-1)**2-(f-n*n)*(n-1+y*(f-n))**2
Al
Sysop: | Keyop |
---|---|
Location: | Huddersfield, West Yorkshire, UK |
Users: | 113 |
Nodes: | 8 (1 / 7) |
Uptime: | 32:09:53 |
Calls: | 2,470 |
Calls today: | 1 |
Files: | 8,630 |
Messages: | 1,893,757 |